Identification of grapevine marker genes for early, non‐destructive Eutypa lata infection diagnosis. (15th July 2013) - Camps, C.; Kappel, C.; Lecomte, P.; Léon, C.; Coutos‐Thévenot, P.; Delrot, S.; Gomès, E.
<x xml:space="preserve">Abstract</x> Eutypa lata is the causal agent of eutypa dieback, a highly damaging trunk disease affecting all grape‐growing areas, with currently neither an efficient curative treatment nor an early non‐destructive diagnostic method. The present work was carried out to discover grapevine genes expressed in response to the presence of E. lata that could be useful to develop an early (before visible foliar symptoms) and non‐destructive (using grapevine leaves) diagnostic tool. Microarray analyses were carried out from (i) infected plants showing characteristic E. lata foliar and vascular symptoms and positive pathogen recovery from vascular lesions (S+R+), (ii) infected plants showing no symptoms (S−R+), and (iii) symptomless plants with negative pathogen recovery (S−R−). Vineyard and greenhouse‐grown plants, naturally or artificially infected respectively, and uninoculated controls were characterized and leaf RNA was hybridized with 15k operon grapevine oligonucleotide microarrays. Among the grapevine genes differentially expressed between S−R+ and S−R− plants in greenhouse and vineyard conditions, 10 were highlighted as robust candidate genes for diagnosis: seven were specifically involved in response to infection and three were associated with symptom absence. Five were confirmed to be effective diagnostic marker genes usable in a qRT‐PCR‐based test performed on RNA extracted from grapevine leaves cultivated in either greenhouse or vineyard conditions. Furthermore, their expression profiles in response to infection with E. lata or other major grapevine fungi (Erysiphe necator, Plasmopara viticola, Botrytis cinerea) could be distinguished. The usefulness of these genes to develop an early and non‐destructive method for diagnosis of E. lata infection is discussed with regard to the advantages and drawbacks of previous E. lata diagnostic studies.